PENGARUH REKRUTMEN, FASILITAS OLAHRAGA, DAN PEMBERDAYAAN TERHADAP MOTIVASI SERTA DAMPAKNYA PADA PRESTASI ATLET DI PUSAT PEMBINAAN LATIHAN PELAJAR (PLPP) DAN PUSAT PEMBINAAN LATIHAN DAERAH (PPLD) ACEH - Rusdi Rusdi; Damrus Damrus (universitas teuku umar, 2019)
This survey examines relationship between recruitment, sport facilities and empowerment through motivation toward athletes’ prestations. The survey took 119 athletes as data whose included in Pusat Pembinaan Latihan Pelajar (PLPP) dan Pusat Pembinaan Latihan Daerah (PPLD) Aceh. This research used path analysis to analyze the data and finds that recruitment, sport facilities and empowerment have an impact to the motivation and athletes’ prestations directly and indirectly. Through that condition indirectly all the exogenous factors have impact to athletes’ prestations. Key words : recruitment, sport facilities, empowerment, motivation, athletes’ prestations